Diminished Antimicrobial Peptide and Antifungal Antibiotic Activities against Candida albicans in Denture Adhesive - Amber M. Bates; Jorge L. Garaicoa; Carol L. Fischer; Kim A. Brogden (MDPI AG, 2017)
The underlying causes of denture stomatitis may be related to the long-term use of adhesives, which may predispose individuals to oral candidiasis. In this study, we hypothesize that antimicrobial peptides and antifungal antibiotics have diminished anti-Candida activities in denture adhesive. To show this, nine antimicrobial peptides and five antifungal antibiotics with and without 1.0% denture adhesive were incubated with Candida albicans strains ATCC 64124 and HMV4C in radial diffusion assays. In gels with 1.0% adhesive, HNP-1, HBD2, HBD3, IP-10, LL37 (only one strain), histatin 5 (only one strain), lactoferricin B, and SMAP28 showed diminished activity against C. albicans. In gels with 1.0% adhesive, amphotericin B and chlorhexidine dihydrochloride were active against both strains of C. albicans. These results suggest that denture adhesive may inactivate innate immune mediators in the oral cavity increasing the risk of C. albicans infections, but inclusion of antifungal antibiotics to denture adhesive may aid in prevention or treatment of Candida infections and denture stomatitis.